Czech Trail Anyone can do it - Martin, Úbl (Jota, 2023)
How come anyone can do a long-distance trail around the Czech Republic? How does a trip made by a group of friends become an official trail that makes it into Forbes magazine alongside Serena Williams and into the world's long-distance routes? Why is it better not to bring a sleeping bag that has a thermal quality suitable for beach sleeping in Morocco? And why have many animals already taken to the trail, but not yet a kangaroo? This combination of lyrical, if sometimes scary, chapters on each section, comically dramatical stories of people who have hiked the trail, and backyard-science tips on how to get started, offers everything you wanted to know about the Czech Trail but were afraid to ask!
Keywords: Sport, zdraví a životní styl